Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Enhancing transportation system resilience under earthquake-induced geohazards: a framework for cross-regional rescue - Damin Zhou; Li Peng; Rui Guo; Zhousong Jiang; Muzi Li (Transportation Research Part D: Transport and Environment, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Five undescribed compounds isolated from Gerbera delavayi with their anti-inflammatory activity - Li Jiang; Yang Wang; Zeng-Dan Ran; Ding-Yan Lu; Rui-Xi Li; Jia Sun; Yong Huang; Xue Ma; Yong-Jun Li (Phytochemistry, 2026)

Fabrication of food-derived bigels beads for the co-delivery of hydrophobic and hydrophilic bioactives: insights into environmental responsiveness and release mechanisms - Rongrong Zhang; Rui Fan; Kai Qi; Jinchi Jiang; Mingzhou Yu; Yiyang Yu; Wenge Yang; Wenhui Li; Yonghong Hu (Food Research International, 2026)

Continuous versus discontinuous biodegradable film mulching in maize: A five-year field study on soil carbon sequestration, productivity, and microplastic legacy - Kai Wang; Xiao Li; Shiyan Sun; Gary Y. Gan; Ying Zhao; Qiang Li; Jiangxin Gu; Rui Jiang (Field Crops Research, 2026)

Managing nitrate pollution in mixed land-use watersheds: source attribution and removal revealed by isotopes and 15N pairing - Jian Zhang; Hao Jiang; Yanping Li; Wenshi Zhang; Wenlu Lan; Junlin Shu; Xin Luo; Rui Zhang; Ke Pan (Ecological Engineering, 2026)

NIR-responsive mesoporous core-shell nanoplatform with oxygen self-supply and cascade targeting for reversing doxorubicin resistance via synergistic chemo-phototherapy - Yufeng Li; Yuping Jiang; Kexuan Wang; Xinyi Liu; Rui Yang; Lu Han; Tao He; Na Li; Da Huo (Chemical Engineering Journal, 2026)

Impact of complex mountainous terrain on the development of strong convective storms: A WRF simulation case study in Southeastern Yunnan Province, China - Cong Jiang; Wenjie Jin; Xin Yin; Chen Li; Rui Mao; Liyun Yin (Atmospheric Research, 2026)

Microplastics-induced effects on membrane fouling and effluent quality in MBRs for landfill leachate treatment under long-term operation - Shijie Bian; Jingwei Yan; Timing Jiang; Huying Li; Rui Cai; Wen Li; Jingjing Shi; Fan Yang; Sha Liang; Huabo Duan; Wenbo Yu; Shushan Yuan; et al. (Waste Management, 2026)

Utilization of spent biochar as a novel adsorbent and catalyst for the removal of ciprofloxacin from water: Insights into the performance and mechanisms - Xiaohong Hu; Tao Jiang; Bing Wang; Rui Li (Journal of Environmental Chemical Engineering, 2026)

Co-inoculation of lactic acid bacteria improves silage quality and mitigates antibiotic resistance gene transmission by restructuring the microbial community in hybrid Pennisetum silage - Duoting Wu; Wan Zhong; Zhisheng Wang; Xinyan Tao; Liyuan Shi; Peng Dai; Fali Wu; Yahui Jiang; Quanhui Peng; Jianxin Xiao; Yiping Tang; Huawei Zou; et al. (Journal of Environmental Chemical Engineering, 2026)

Effect of food components on arsenic metabolism by the gut microbiota using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME) - Yue Wu; Shimao Xiong; Xiyan Jiang; Peng Xiao; Fang Zhao; Rui Li; Syed Ali Hassan; Xiaolin Cai; Zhengyi Hu; Dennis Sandris Nielsen; Naiyi Yin; Yanshan Cui (Food Research International, 2026)

Multi-omics combined with simulated fermentation model for elucidation of variation patterns of lipids and volatiles and its mechanism during black tea fermentation - Linchi Niu; Yuning Feng; Shan Zhang; Zhizhen Fang; Rui Liang; Zhenxing Xu; Xujiang Shan; Qinghua Zhou; Haibo Yuan; Yongwen Jiang; Jia Li (Food Chemistry, 2026)

Machine learning models reveal the spatial distribution and key environmental drivers of Coilia nasus in East China Sea's coastal waters - Zeyu Xiao; Jiarong Shen; Haoran Wang; Rijin Jiang; Jianxiong Li; Rui Yin; Jiaying Zeng; Mingyuan Cui (Estuarine, Coastal and Shelf Science, 2026)

Flow velocity and turbulent kinetic energy effects on Crassostrea ariakensis larval settlement: Lab and CFD insights - Nan-nan Li; Rui-liang Fan; Long-ling Ouyang; Yuan-ge Chen; Jia-feng Fang; Wei Jiang; Nian Wei; Wei-min Quan (Estuarine, Coastal and Shelf Science, 2026)

Rapid inverse design of double-curved beams for multi-stable metamaterials based on prescribed deformation histories through artificial neural network - Chun-Zheng Zhao; Xin Wang; Rui Zhang; Yongfeng Jiang; Haibo Ji; Zhen Li; Bingyang Li; Pengfei Wang; Feng Jin; Tian Jian Lu (Engineering Structures, 2026)

Targeting the oxidation-inflammation-senescence axis in osteoarthritis with a single-atom iridium nanozyme - Yunsheng Jiang; Rui Li; Yun Ning; Zhiyu Chen; Tao Li; Cheng Chen (Chemical Engineering Journal, 2026)

Janus dual-nitride heterostructure on nanoporous metal for highly selective urea oxidation-assisted hydrogen production - Zhi-Lan Zhou; Jin-Peng Li; Ying Wang; Rui-Qi Yao; Xin-Ying Sun; Shu-Pei Zeng; Yun-Fei Chang; Gao-Feng Han; Tong-Hui Wang; Zi Wen; Hang Shi; Xing-You Lang; et al. (Chemical Engineering Journal, 2026)

Enhanced degradation of sulfamethoxazole in dielectric barrier discharge plasma via Zn tetrahedral site doping-mediated d-band center engineering of CoFe2O4 - Xiaojing Wang; Rui Cao; Na Huang; Mengmeng Du; Mingyao Yuan; Jia Ma; Fan Zhang; Jiaqi Jiang; Zhenxing Zeng; Yanzong Zhang; Zhilin Li; Shihuai Deng (Chemical Engineering Journal, 2026)

Low-cost pillar-ligand engineering toward ultramicroporous MOFs for efficient SF6/N2 separation - Biao Fu; Hui-Ting Zheng; Rui-Ming Li; Duo Yue; Liang Song; Zhang-Wen Wei; Robert Langer; Mihail Barboiu; Ji-Jun Jiang; Cheng-Yong Su (Chemical Engineering Journal, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

Equivalent emissivity correction of the blackbody on-board MWRI-RM - Dong Ke-Song; Xing Rui-Xian; Bai Chuan; XU Jing; Meng Wan-Ting; He Jia-Kai; Jiang Li-Fei (International Journal of Remote Sensing, 2026)

Transcriptome and metabolome analysis reveals that cuproptosis in bovine cumulus cells triggers the intercellular transmission of senescence and mitochondrial dysfunction to impair oocyte quality - Hong Xu; Tian Tian; Dan Xu; Xiaoxue Du; Rui Su; Jinghong Liang; Ying Liu; Yuqing Zhang; Chang Liu; Shuang Liang; Qingying Li; Deli Ding; et al. (Theriogenology, 2026)

Research on the intelligent obstacle avoidance and path optimization approaches for ship navigation in ice regions - Zhichen Liu; Sihui Wu; Mingyuan Jiang; Ying Li; Rui Gao; Jianan Luo (Ocean Engineering, 2026)

Divergent effects of biodegradable and conventional microplastics on denitrification in soils: Mechanisms governing N₂O emission and product stoichiometry - Hao Zhang; Xiao Li; Minhang Zhu; Rui Wang; Jinbo Zhang; Christoph Müller; Rui Jiang (Journal of Hazardous Materials, 2026)

Adaptive genetic trade-offs govern the enantioselective degradation and horizontal transfer of ibuprofen catabolic genes - Weihao Zhu; Mingli Jiang; Rui Fan; Kaihua Pan; Shenghao Wang; Lu Huang; Qiantong Ru; Yinhu Jiang; Qian Li; Qian Zhu; Mingliang Zhang; Zhijian Ke; et al. (Journal of Hazardous Materials, 2026)

Interfacial electron redistribution stabilizes Cu-centered redox cycling for efficient Fenton-like catalysis - Xiao-Ying Li; Ruo-Lan Xu; Ren Zhu; Ting-Yu Zhang; Wen-Rui Wang; Wu-Jun Liu; Hong Jiang (Journal of Cleaner Production, 2026)

How phosphorus enrichment regulates the microbial community resistance and multifunctions tolerance to drying–rewetting cycles in paddy fields: the critical role of stoichiometry - Jiaying Wang; Yi Xu; Tinghong Fu; Guoxiang You; Rui Wang; Tianyun Li; Zewei Jiang; Shihong Yang (Journal of Environmental Management, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

Sex-specific associations between prenatal PM2.5 exposure and reproductive hormone levels in offspring aged 1–2 years: A prospective birth cohort study - Wenpu Shao; Shengli Jiang; Yudiyang Ma; Ning Chen; Zhiping Niu; Rui Tang; Meiqi Xing; Lei Zheng; Xinru Zhao; Bin Sun; Haibo Li; Ziyi Zhou; et al. (Environmental Research, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

Environment-responsive multi-enzymed Cu/Cu2O@NC nanorhombic nanoplatform for infected wound antimicrobial treatment - Ji Cheng; Hao Zhang; Yueting Jiang; Zuojia guo; Rui Liu; Xiantao Lin; Hanjin Lu; Yunjun zhang; Wenxuan Fan; Ding Luo; Jinghua Li (Chemical Engineering Journal, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Folic acid alleviates heat stress-induced ovarian dysfunction in dairy cows via modulation of follicular fluid metabolism and ABC transporter activity - Yaochang Wei; Yifan Yang; Yifan Li; Zhuangsheng Wang; Tingting Deng; Xiaojiao Hu; Xuefeng Jiang; Rui Xiao; Yanfang Wu; Suzhu Qing; Yongsheng Wang (Animal Reproduction Science, 2026)

Correction to: Antibacterial activity and mechanism of rutin in UV-A light treatment against Escherichia coli O157:H7 - Jiahui Wang; Yuzhang Zhu; Tao Liu; Xiangyu Hong; Mi Liu; Rui Zhou; Xianke Li; Mingguo Jiang; Lifang Yang (Archives of Microbiology, 2026)

A topology-aware direction-adaptive multitask evolutionary algorithm - Yuxin Chen; Lizhong Yao; Rui Li; Pengjie Qin; Peng Jiang; Jun Yi (Swarm and Evolutionary Computation, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Numerical study of the flow field effect of turbulent reef units under different deployment configurations - Jiayi Wang; Rui Pan; Zhu Li; Xiaoran Liu; Qiwen Liang; Zhaoyang Jiang (Ocean Engineering, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

From acute defense to prolonged metabolic homeostasis: Insights into microalgae responses to PVC microplastic exposure - Jia Liang; Xiao Tan; Jiawei Li; J. Paul Chen; Yuanyuan Tang; Zhipeng Duan; Jiang Huang; Rui Zhu (Journal of Hazardous Materials, 2026)

Mitigating bioaerosol exposure risks in high-traffic clinics: Experimental and numerical optimization of air purifier interventions - Yongxin Wang; Zhijian Liu; Lei Jiang; Zirun Shi; Zijian Li; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Journal of Hazardous Materials, 2026)

Magnetite-phase steel slag-peroxymonosulfate promoted volatile fatty acids recovery from anaerobic fermentation of food waste: Substrates structure disruption and metabolic regulation - Xiupeng Jiang; Wei Wang; Youcai Zhao; Wenxiao Zhang; Xi Li; Rui Zhang; Xiaoya Li; Tao Zhou (Journal of Environmental Chemical Engineering, 2026)

Water and nutrient mechanism of bioretention systems under plant-filler synergy and seasonal dynamic regulation - Chunbo Jiang; Rui He; Jian Yuan; Hong Chen; Jiake Li (Journal of Environmental Chemical Engineering, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

Corrigendum to “A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization” [Chemical Engineering Journal 532 (2026) 174382] - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Defect-engineered Bi2O2S/Co3O4 heterostructure on sunflower pith for synergistic solar-driven interfacial evaporation and VOC degradation - Tingting Jiang; Siyu Huang; Zhuo Li; Rui Zhao; Haifeng Zhang (Chemical Engineering Journal, 2026)

Development of a triplex RT-qPCR assay for rapid and accurate detection of porcine rotavirus, porcine epidemic diarrhea virus, and porcine deltacoronavirus - Yuhan Yang; Xingyu Xiao; Meixuan Ren; Ningning Jiang; Xiaoxu Xie; Xue Zheng; Rui Yin; Shiyu Luan; Jingnan Wang; Peng Li (Veterinary Research Communications, 2026)

Microbial inoculation in green roofs: progress, challenges and ecological regulation strategies - Nan Yang; Hechen Li; Yihan Wang; Pingrui Jiang; Shaobo Gao; Hongyuan Li; Rui Hua; Xinjian Shi; Guang Hao (Urban Ecosystems, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

MECP2T203M mutation disrupts neurogenesis in human cerebral organoids by altering chromatin dynamics and transcriptional regulation - Zhihong Song; Qian Zhu; Rui Yang; Huihui Jiang; Ying Li; Liping Chen; Ting Wang; Yan Wu; Yan Liu; Haitao Wu (Science China Life Sciences, 2026)

Antibacterial activity and mechanism of rutin in UV‑A light treatment against Escherichia coli O157:H7 - Jiahui Wang; Yuzhang Zhu; Tao Liu; Xiangyu Hong; Mi Liu; Rui Zhou; Xianke Li; Mingguo Jiang; Lifang Yang (Archives of Microbiology, 2026)

Histamine regulation in shaping spindle refractoriness: a computational modeling study - Bo Wang; Qiang Li; Wen-Hua Wang; Wan-Rong Zan; Yi-Ming Li; Jiang-Ling Song; Rui Zhang (Journal of Computational Neuroscience, 2026)

Cross-species comparative transcriptomic analysis of spermatozoa reveals species-specific regulatory networks linked to fertilization-associated genes in cattle, sheep and goats - Yue Zhao; Linfeng Bai; Qiqi Jiang; Hao Xiao; Fangyuan Liu; Bilige Wuyun; Rihan Wu; Chunxia Hao; Rui Ding; Peng Yuan; Lizhi Wang; Ying Lu; et al. (Science China Life Sciences, 2026)

Lithium Enhances Survival Bias Associated with the Lateral Habenula Suppression - Kunlin Liu; Rui Zhu; Haoyue Guo; Jinghuan Li; Qianfu Wang; Yi He; Chenggang Zhu; Zheng Ma; Xiaodan Jiang; Jack van Honk; Jin Bao (Neuroscience Bulletin, 2026)

Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Micro-nano biochar interfaces promote adsorption-reduction coupling to accelerate bioelectrodechlorination in groundwater - Zena Zhang; Miao Lv; Rui Wang; Bo Wang; Ruoyu Du; Yuxuan Lou; Chunlin Wang; Xiaodun Jiang; Hai Hou; Zhiling Li; Fan Chen (Journal of Hazardous Materials, 2026)

Study on the synergistic effect of coal-oil co-liquefaction and analysis of liquefied oil products - Jin Jiang; Guanghua Yang; Ting Liu; Xiaodong Zhou; Xiaohui Li; Rui Sheng; Lang Liu (Fuel, 2026)

CO2-temperature-water nexus reshaping cherry tomato flavor: Multimodal sensing with E-nose and GC-IMS - Rui Li; Xinru Ren; Yilin Wang; Mengyan Jiang; Rongqun Wang; Zhi Zhang (Food Chemistry, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

Evaluation of the aerosol transmission patterns and the airflow organization effectiveness in the respiratory outpatient clinic - Yongxin Wang; Lei Jiang; Zhijian Liu; Duo Cai; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Building and Environment, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Short-term organic fertilizer substitution: effects on crop yield and soil phosphorus dynamics in a rice-rapeseed rotation system - Hui Wang; Wenlong Cheng; Shang Han; Shan Tang; Fahui Jiang; Rongyan Bu; Min Li; Rui Zhu; Mengmeng Tang; Zhenghua Xu; Ji Wu (Journal of Soils and Sediments, 2026)

Vitamin C mitigates early auditory cortical hyperexcitability and antioxidant imbalance induced by acute intermittent hypoxia - Yue Wu; Tao Li; Wanxin Cao; Rui Fan; Hailing Jiang; Jiachen Han; Furong Ma; Yan Yan (Experimental Brain Research, 2026)

A multi-strategy integrated heuristic algorithm for the container relocation problem in automated container terminal yards - Yipeng Jiang; Yong Zhang; Lei Zhang; Zhen Li; Chengji Liang; Rui Zhao; Yu Wang; Panlong Wang (Frontiers in Marine Science, 2026)
As the operational scale of automated container terminals continues to expand, the impact of the container relocation problem on operational efficiency and cost has be-come increasingly significant. To address the issues of excessive relocations and low operational efficiency during container retrieval within a bay, a container relocation optimization model for the yard is developed. On this basis, a bay-oriented heuristic algorithm is proposed by incorporating practical operational rules and operational experience. The algorithm prioritizes empty stacks, non-blocking stacks, and stacks with the minimum number of blocking containers. It further integrates the nearest-placement rule and safety height constraints to achieve efficient and rational relocation decisions for blocking containers. Numerical experiments with different problem scales are conducted to validate the effectiveness of the proposed method. The results show that, in small-scale instances, the proposed algorithm effectively reduces the number of relocations. In large-scale instances, its advantage becomes more pronounced as the problem size increases. Compared with the traditional nearest-placement rule, the proposed algorithm consistently achieves superior performance across different scales: the number of relocations is reduced by up to 15, the relocation rate decreases by an average of 56%, and the operational cost is reduced by approximately 35.85% on average.

Dihydromyricetin attenuates LPS-induced liver injury in chicks through the JNK signaling pathway - Lina Jia; Jiarui Liu; Zhenghua Ji; Liang Yuan; Yingchao Gong; Xinru Jiang; Xianan Fan; Changwen Li; Rui Li; Haoran Wang; Fangping Liu (Research in Veterinary Science, 2026)

Report on the complete mitochondrial genome of the critically endangered and endemic Lauraceae plant Syndiclis anlungensis in China - Lang Huang; Dongzhen Jiang; Yanbing Yang; Rui Chen; Zhi Li; Lei Zhou; Xu Xiao (Plant Gene, 2026)

An adaptive spatiotemporal coupling approach for dynamic collision risk perception and quantification in intelligent vessels - Zhichen Liu; Mingyuan Jiang; Ying Li; Rui Gao; Yu Du; Jianan Luo (Ocean Engineering, 2026)

Centralized mechanical e-waste dismantling is associated with lower farmland soil heavy metal pollution and carbon emission intensity - Yu Zhang; Ming-jiang He; Wei-jun Fu; Jie Wang; Ke-li Zhao; Xiang-rui Xu; Ji-zi Wu (Journal of Environmental Chemical Engineering, 2026)

Genome-wide association study of wheat (Triticum aestivum L.) starch pasting properties - Jiahui Jiang; Hao Chang; Yongji Ma; Rui Jin; Rui Yu; Zhenhua Lu; Tianqi Bai; Yufeng Xu; Ruili Gou; Chengyu Lian; Wenting Zhang; Yingang Hu; et al. (Journal of Cereal Science, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

Relationship of catalytic performance and catalyst structure evolution based on pressurized CH4-CO2 reforming reaction over carbon-supported Co-Ir alloy catalysts - Wen Tang; Jing-Pei Cao; Xiao-Yan Zhao; Dan Xie; Kai-Rui Luan; Chang-Jiang Li; Qi-Ming She; Tungalagtamir Bold (Fuel, 2026)

Linking environmental concentrations to cytotoxic mechanisms in second-hand vapor exposure of electronic cigarette via an integrated approach for in vitro toxicity assessment - Tong Cui; Yanpeng Li; Rui Lu; Zhenyu Niu; Xingtao Jiang (Environmental Pollution, 2026)

Mimicking leaves hierarchical differential pore architecture integrated with electric/magnetic inverse gradient structure for green EMI shielding and thermal infrared stealth - Dingwen Yin; Jinbao Li; Rui Cheng; Huijuan Xiu; Gengmei Liu; Feiguo Hua; Xuanchen Jiang; Yuxin Qin; Xia Wang (Chemical Engineering Journal, 2026)

Coordinatively robust and toughen plant protein adhesives via the synergy of oligomer domain cross-linking and hierarchical dissipation architecture - Wujie Huang; Zhenghui Lei; Ao zhang; Rui Xu; Jiawei Shao; Xianwei Wang; Shuaicheng Jiang; Jianzhang Li; Xiaona Li (Chemical Engineering Journal, 2026)

Interface-engineered MXene/OCNT fibers for high-performance wearable supercapacitors - Rui Wang; Xupu Jiang; Ting Ding; Wujun Ma; Chuntao Lan; Min Li (Chemical Engineering Journal, 2026)

Multi-scale evaluation of ERA5-land downward shortwave radiation and its implications for building energy simulation over China - Song Jiang; Jingfu Cao; Mingcai Li; Rui Miao; Minjie Yu (Theoretical and Applied Climatology, 2026)

Diffusion Model-Based Multi-Channel EEG Representation and Forecasting for Early Epileptic Seizure Warning - Zekun Jiang; Wei Dai; Qu Wei; Ziyuan Qin; Rui Wei; Mianyang Li; Xiaolong Chen; Ying Huo; Jingyun Liu; Kang Li; Le Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Global evaluation of the IRI-2020 ionospheric model using multi-source observations in 2022 - Chunhua Jiang; Rui Gao; Liang Chen; Huizhong Zhu; Min Li; Xiang Gao (Advances in Space Research, 2026)

Metabolic inflexibility across heart failure phenotypes: mechanisms and type-specific therapeutic implications - Li Chen; Xin-Rui Yang; Yan Jiang; Shi-Qi Cheng; Zhen-Xun Wan; Jin-Wen Wu; Ming-Tai Chen; Yuan-Yuan Li; Gang Luo; Meng-Nan Liu (Apoptosis, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

New 14,15-dinor- neo -clerodane and neo -clerodane diterpenoids from Ajuga macrosperma Wall. ex benth - Yi-huan Li; Yi-hang Ba; Jian-fen Xiao; Shuai Chen; Tian-qing Zhu; Kai-xiang Liu; Hong-ping He; Hua-yi Jiang; Rui Yang (Natural Product Research, 2026)

Hormonally and chemically induced male-to-female sex reversal is independent of Y-chromosome number in common carp - Kuangxin Chen; Yuanqi Guo; Yi Rong; Zhaoxian Li; Mouyan Jiang; Rui Li; Xiya Zhang; Yongming Li; Yulai Wei; Yanlong Song; Ji Chen; Binbin Tao; et al. (Aquaculture, 2026)

An automated vertebral heart scale measurement tool based on deep learning: Facilitating screening for prevention of canine cardiomegaly - Jing Chang; Rui Qin; Huijie Jiang; Jinfan Wei; Haotian Gong; Shijun Li; He Gong; Shuang Zhang (Preventive Veterinary Medicine, 2026)

A preliminary assessment of ocean wave parameter retrieval and wave energy estimation using spaceborne BDS-R data - Jinwei Bu; Shuhui Liu; Shunshuang Xu; Hui Yang; Tongsu Xiang; Xin He; Yuhang Jiang; Rui Li (Ocean Engineering, 2026)

Shift in orbital-scale climate response under the coupling of ice sheet and monsoon during the Late Oligocene: Sedimentary records from the East China Sea Shelf Basin - Yingkun Cui; Fujie Jiang; Xianke He; Yichen Liu; Wenji Wang; Rui Zhang; Yinghui Liu; Zhuo Li; Zhenguo Qi; Bo Xu; Hang lv; Jiming Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Extreme rainfall intensifies nitrogen responses through baseflow in arid and semi-arid river basins - Jinghui Dou; Rui Xia; Zixuan Tang; Zhen Huang; Xiaohui Jiang; Kai Zhang; Lina Li; Chao Yan (Journal of Hydrology, 2026)

A machine learning approach coupling immediate and lagged drivers to predict sand and dust storms in Northern China - Mile Wang; Kunxia Yu; Peng Li; Zhanbin Li; Rui Yan; Zixia Jiang; Xue Li; Lu Jia (Journal of Environmental Management, 2026)

Ultra-low temperature adsorption of propane to achieve layered Ni3V2O8/NiO synergistic catalysed oxidative dehydrogenation of propane to propylene - Rui Liao; Yun Yang; Peiting Jiang; Fengyu Ji; Yuhang Qian; Lulu Li; Xuyu Wang; Xinwei Zhou; Hongbing Ji (Fuel, 2026)

Superabsorbent and antimicrobial cryogel pads based on gelatin, sodium alginate and zinc oxide nanoparticles: Preparation, characterization and enhanced preservation of aquatic products - Jiaxuan Fang; Siyu Wu; Xiali Zeng; Rui Li; Zhenting Huo; Zhongjie Yu; Qingbao Ma; Di Sun; Yu Liu; Wei Jiang (Food Research International, 2026)

Co-fermentation with autochthonous Levilactobacillus brevis and Lactiplantibacillus plantarum modulates metabolome and volatile profiles to improve the quality and safety of fermented chopped chili - Wenkai Jiang; Qian Yang; Luyao Xiao; Xia Fan; Menghan Zhong; Mahsa Ghahvechi Chaeipeima; Kai Ma; Changliang Zhang; Xin Rui; Wei Li (Food Research International, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Strain-specific effects of infant-derived Bifidobacterium on gut microbiota modulation and mucus barrier responses in Salmonella infection - Xiaogan Zhao; Mahsa Ghahvechi Chaeipeima; Luyao Xiao; Xia Fan; Wenkai Jiang; Xiran Jia; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Bioscience, 2026)

Biotransport and biotransformation of arsenic in earthworm tissues: Advancing vermiremediation strategies of soil contamination - Yunxiang Xu; Muyuan Wang; Yizhao Wu; Yifan Zhang; Rui Jiang; Qi Zhao; Jibao Jiang; Hao Qiu; Yinsheng Li (Chemical Engineering Journal, 2026)

A Novel Elastoplastic Dynamic Damage Constitutive Model and Numerical Implementation of Rock Under True Triaxial Multistage Disturbance - Zhi Zheng; Yihuai Zhang; Guoxiong Mei; Haibo Jiang; Wei Wang; Rui Pan; Shaojun Li (Rock Mechanics and Rock Engineering, 2026)

Identification, expression, and insecticidal activity analysis of a novel cry toxin gene from Bacillus thuringiensis Gxun777-1 - Qi Gao; Tianbao Yang; Xixi Li; Rui Chen; Mingguo Jiang; Yan Zhou (World Journal of Microbiology and Biotechnology, 2026)

Evaluation and characterization of aphid (Aphis craccivora) resistance in selected alfalfa genotypes - Xin Jiang; Jing Tian; Gang Li; Guy Smagghe; Zhong-Yi Li; Dao-Chao Jin; Zhou Li; Rui Dong; Xin-Yao Gu (Crop Protection, 2026)

Effects of bacteria-microalgae immobilization on physiology, immunity, microbial composition, and vibriosis resistance of sea cucumber (Apostichopus japonicus) - Xuda Wang; Zunchun Zhou; Ying Dong; Rui Mi; Jingwei Jiang; Danni Liu; Bo Ye; Xiaoyue Wang; Zhenjun Zhao; Boxue Yang; Shilei Li (Aquaculture, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Erlvejunzuo, a gallic acid-derived thiadiazole, inhibits glucose biosynthesis and confers broad-spectrum antifungal activity - Manman Zhang; Chengke Zhang; Yihan Jiang; Li Wu; Rui Zhang; Fengquan Liu; Cheng Li (Pesticide Biochemistry and Physiology, 2026)

Effect of densification on dimensional stability and water absorption behavior of pine - Ning Jiang; Xintao Zhao; Qingchuan Lu; Emily Treacher; Alberto Leonardi; Xuejiao Li; Rui Li; Zhongsen Zhang; Thomas James Marrow (Journal of Cleaner Production, 2026)

Secondary salinization in facility agricultural soils detrimentally affects the spatial distribution of earthworm communities: dominant drivers and ecological risks - Yifan Zhang; Yizhao Wu; Muyuan Wang; Rui Jiang; Yunxiang Xu; Qi Zhao; Jibao Jiang; Ke Song; Weiguang Lv; Yinsheng Li (Journal of Environmental Management, 2026)

Immobilization of arsenic and antimony in contaminated soil by nano silica–biogenic Fe (Hydr)oxide composites: Soil properties and microbial community impacts - Rui Xu; Chenyang Yin; Qian Li; Guangfei Qu; Zhenguo Wu; Lang Liao; Zhe Yin; Yan Zhang; Yongbin Yang; Tao Jiang (Journal of Environmental Chemical Engineering, 2026)

Triple-synergistic nanotherapeutics for acute and chronic colitis management via programmable multidimensional modulation - Penghui Wang; Yue Zhao; Ning Tian; Xiangling Liu; Tenghui Tian; Difu Zhu; Fangbing Liu; Hengyan Liu; Ling Li; Zhiyu Ren; Deok Chun Yang; Lei Zhao; et al. (Chemical Engineering Journal, 2026)

Functionalizing 3D DNA crystals by replacing non-framework strands - Xinyu Feng; Li Xu; Yunhan Zhang; Shuheng Wei; Dongbao Yao; Huichao Chen; Yueye Wang; Yujing Wu; Hui Hou; Xiao Cui; Qian Meng; Yue Gu; et al. (Chemical Engineering Journal, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Trpa1 activation suppresses luteinizing hormone via Activin/Follistatin Axis under cold stress in Nile Tilapia - Jing Li; Haomiao Dong; Zhikai Cao; Rui Dong; Quan Jiang (Aquaculture, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Alpaca nanobody-based sandwich ELISA for specific detection of Salmonella enteritidis in chicken - Liang Yuan; Shibo Wang; Yani Ren; Zhenghua Ji; Xinru Jiang; Beili Hao; Shuangshuang Hao; Xiaoxi Han; Changwen Li; Yicong Chang; Rui Li; Fangping Liu (Food Control, 2026)

A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Bioengineered functional scaffolds co-loaded with osteonectin and HA-internalizing osteoblasts for boosting bone regeneration - Wei Yang; Qin Zou; Chenxin Wang; Yuankun Ren; Rui Zhang; Mingyue Lin; Xueqi Zhang; Yu Liu; Boyang Wang; Wei Li; Li Jiang; Xiyu Li (Chemical Engineering Journal, 2026)

How biodegradable mulching alters soil nitrogen transformations to enhance soil nitrogen supply and influence gas emissions in a maize cropping system - Hao Zhang; Kai Wang; Jinbo Zhang; Christoph Müller; Dianyuan Ding; Qiang Li; Hengliang Tang; Rui Jiang (Plant and Soil, 2026)

Glaucine suppresses IL-16/CD4 to alleviate neuropathic pain via spinal p56lck-NMDA receptor signaling - Xue Li; Rui Wang; Xiaonan Ma; Jin Yang; Shen Zhang; Zimeng Zhang; Han Jiang; Jihua Liu; Boyang Yu; Wenling Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Anthropogenic heat amplification in industrial zones: Unraveling heat stress risk heterogeneity in river-sea dual-core cities - Yujie Li; Jingfu Cao; Mingcai Li; Song Jiang; Jie Yang; Rui Xin; Ping Qu; Jing Chen; Jing Wang (Sustainable Cities and Society, 2026)

The impact of precipitation and exposed rocks on the soil and water leakage processes in the karst depressions-sinkhole system: Insights from a laboratory simulation experiment - Feiyang Cai; Rui Li; Jiang Yuan; Benjin Yu (Soil and Tillage Research, 2026)

A bHLH transcription factor negatively regulates effective panicle number and grain yield by modulating auxin transport and distribution in rice - Tao Yang; Rui Zhu; Jinlong Li; Yulong Wang; Lei Zhou; Qiaoqiao Zhao; Ningjia Jiang; An Zeng; Yanli Qin; Haixia Liu; Chenyu Xia; Shichen Han; et al. (Molecular Plant, 2026)

Determining the source contributions of dissolved organophosphorus compounds in lake water utilizing FT-ICR-MS and PCA-APCS-MLR receptor models - Xinrui Jiang; Yao Du; Mengze Li; Rui Xu; Tianming Wu; Baisong Deng; Dandan Si; Wen Zhang; Jingwen Yu; Yanxin Wang (Journal of Hydrology, 2026)

Associations of prenatal exposure to organophosphate, pyrethroid, and neonicotinoid insecticides with maternal and infant urinary reproductive hormones - Ying Li; Ying Jiang; Ruizhen Li; Sha Huang; Ruijia Li; Qing Guo; Pei Leng; Rui Ma; Dingye Zheng; Yuanyuan Li; Shunqing Xu; Wei Xia (Journal of Hazardous Materials, 2026)

Performance analysis of an ammonia-kerosene dual-fuel novel SOFC-turboprop engine aviation hybrid system with chemical heat recovery - Xinyan Xiu; Rui Wang; Cong Wang; Jiwei Fang; Meng Zhao; Chenghao Li; Sibo Wang; Jiang Qin; Hongyan Huang (Fuel, 2026)

Machine learning-enhanced colorimetric and surface-enhanced Raman scattering-based bimodal lateral flow immunoassay for sensitive and simultaneous detection of the residues of lomefloxacin, ofloxacin, and pefloxacin - Minghui Li; Daqi Chen; Yuhuai Guo; Tianxu Li; Wenjie Guo; Rui Feng; Dien Shao; Ziqi Jiang; Ye Li; Jie Zan (Food Chemistry, 2026)

Efficient elimination of highly lethal Vibrio parahaemolyticus in shrimp aquaculture by a vibriophage - Mingrui Li; Huaijin Jiang; Keming Shi; Haoyu Huang; Xiaojun Wang; Fang Li; Ke Pan; Yunlan Yang; Rui Zhang (Fish & Shellfish Immunology, 2026)

Self-adaption ultra-small coordination polymer-incorporated nanofibers for multipronged management of diabetic wounds - Peirong Zhou; Min Jiang; Silei Li; Xuemin Ma; Yajuan Hu; Junliang Chen; Yun He; Gang Tao; Rui Cai (Chemical Engineering Journal, 2026)

Molecular dipole engineering enabled TiO2 electron transport layers for stable quantum-dot light-emitting diodes - Hang Liu; Pei-Li Gao; Bo Li; Hui Bao; Yin-Man Song; Meng-Wei Wang; Ting Ding; Jing Jiang; Rui-Feng Zheng; Feng-Jia Fan; Hai-Zheng Zhong; Kar-Wei Ng; et al. (Chemical Engineering Journal, 2026)

A new isoflavone from processed root barks of Paeonia suffruticosa and their procoagulant activity - Shuo-Guo Li; Rui Yang; Mi-Mi Lu; Shu-Mei Wang; Jiang Meng (Natural Product Research, 2026)

Enhancing geohazard susceptibility mapping with a sample reliability algorithm: a case study in Guangzhou, China - Yuchao Jiang; Yan Gao; Wenlong Li; Rui Chen; Zhiliang Zhang; Quan Yuan; Daixun He (Bulletin of Engineering Geology and the Environment, 2026)

GABPα2β2 tetramer deficiency impairs natural killer cell maturation, compromising cytotoxicity and resistance against melanoma - Weiwei Jia; Wanting Zhong; Shanshan Hao; Zhao Wang; Shuaishuai Niu; Yingdi Xu; Yajiao Zhang; Mingxia Feng; Haitao Jiang; Jiarui Zhang; Danli Song; Peiyao Yan; et al. (Science Bulletin, 2026)

Performance evaluation of an enhanced air-lift internal circulation anaerobic–aerobic integrated reactor for treating real domestic wastewater - Yi Jiang; Muhammad Younas; Rui Zhang; Yizhi Zhang; Siyi Bian; Mingjie Hu; Die Liang; Linshan Yang; Pan Li; Suhui Xia; Wenyang Tao; Yuji Ma; et al. (Journal of Water Process Engineering, 2026)

Migration and transformation mechanism and ecotoxicity of heavy metals in shale gas exploitation: Research progress and challenges - Hualin Zhang; Xiaoliang Jiang; Rui Wang; Tinggang Li (Journal of Hazardous Materials, 2026)

Developing a radio frequency disinfestation technology for red jujubes with BaTiO3 as a filling material: Pest mortality, energy efficiency, and product quality - Xin Ye; Junjie Zheng; Jinsong Zhang; Longlong Jiang; Rui Li; Shaojin Wang (Journal of Food Engineering, 2026)

Photocatalytic carbon dots for food-borne hazards: Antimicrobial and degradation mechanisms and applications in the food industry - Dangfeng Wang; Wangqing Jiang; Likun Ren; Yang Jiang; Yuqiong Meng; Rui Ma; Shulin Wang; Hongyan Guo; Fangchao Cui; Xuepeng Li; Tingting Li; Jianrong Li (Food Research International, 2026)

Efficient bioconversion of corn stover hydrolysates into phenazine-1-carboxylic acid by engineered Pseudomonas chlororaphis for sustainable biopesticide production - Sheng-Jie Yue; Yu-Xuan Li; Kai-Quan Liu; Sheng-Xiao Zhang; Peng Huang; Wei Wang; Xue-Hong Zhang; Xiang-Rui Hao; Lian Jiang; Hong-Bo Hu (Bioresource Technology, 2026)

Integrated Aerobic Exercise and Multisensory Environment Training for Age-related Cognitive Decline via Hippocampal-prefrontal Neural Circuit Modulation - Huawei Lin; Yuxi Qiu; Zhongyi Hu; Liming Chen; Yaling Dai; Tao Jiang; Rui Li; Sinuo Wang; Yajun Cao; Jianhong Li; Huanhuan Liu; Yuwei Ye; et al. (Molecular Neurobiology, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Spatial aggregation trends of cultivated land quality and landscape patterns: A remote sensing analysis - Mengmeng Tang; Wenlong Cheng; Zhengbao Gao; Fahui Jiang; Shang Han; Danyang Xu; Rongyan Bu; Shan Tang; Rui Zhu; Min Li; Hui Wang; Changai Lu; et al. (Applied Soil Ecology, 2026)